Effect of Levilactobacillus brevis TISTR 860 and Lactiplantibacillus plantarum TISTR 951 on gamma-aminobutyric acid content in fermented rice flour and rice noodles (Kanomjeen) - Chittrakhani, Chonnipa; Songsermpong, Sirichai; Trevanich, Sudsai; Sukor, Rashidah (Wiley-Blackwell Publishing, 2022)
This research aimed to reduce the fermentation time of fermented rice flour for fermented rice noodles (Kanomjeen) to 24 h by adding the initial starter cultures, which are Levilactobacillus brevis TISTR 860 (LB) and Lactiplantibacillus plantarum TISTR 951 (LP) alone in rice slurry to achieve the quality and high gamma-aminobutyric acid (GABA) content. The initial pH value of rice slurry was adjusted to 4.5 and enriched with 2% of monosodium glutamate (MSG) before fermentation. LP was able to produce lactic acid and reduced pH better than LB but produced GABA in less content. Expanding fermentation time induced decreasing in viscosity and whiteness of flour. Fermented rice noodles provided better tensile strength and elasticity. In conclusion, LB could produce GABA in the amount of 21.80 mg/100 g dry basis in 24 h with good quality.